Diagnostic Challenges and Management Considerations for Aortic Root Aneurysm in Adult Suspected with Marfan Syndrome: A Case Report - Maharani, Ni Putu Ika Regina; Leoni Leoni; Wibowo, Ganda (Lembaga Pengembangan Kinerja Dosen, 2024)
Aortic aneurysm is an abnormal dilatation of the aorta commonly associated with hereditary genetic disorders such as Marfan syndrome, with an incidence of approximately 5–10 cases per 100,000 people per year, predominantly involving the ascending aorta. Diagnosing Marfan syndrome remains challenging in clinical practice, especially in settings with limited diagnostic resources such as rural areas in Indonesia. This study is a case report describing the diagnostic process and management of a patient with an aortic root aneurysm suspected to be associated with Marfan syndrome. Data were collected from medical records, physical examinations, and supporting investigations such as transthoracic echocardiography (TTE), and were compared with relevant literature and updated clinical guidelines (ESC Guidelines 2024 and Revised Ghent Criteria 2010). The findings showed that a patient presenting with clinical features of Marfan syndrome, including Corrigan’s sign, diastolic murmur, and a systemic score ≥7—had significant aortic root dilatation (7.08 cm) accompanied by severe aortic regurgitation and decreased left ventricular function. Conservative therapy with bisoprolol, candesartan, and standard heart failure medications was administered to stabilize the condition before referral to a tertiary hospital for advanced imaging and surgical planning. Conclusion: This case highlights the importance of comprehensive history taking, careful physical examination, and echocardiography as essential tools for the early diagnosis of aortic aneurysm related to Marfan syndrome, particularly in healthcare facilities with limited diagnostic resources. Early detection and proper management play a crucial role in preventing fatal complications and reducing mortality.